Employing the joint venture format for upgrading waqf assets: concerns and alternatives - Sadique, Muhammad Abdurrahman (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), IIUM, 2025)
The research deals with formulating viable means and structures for upgrading existing awqaf assets that are in line with the Islamic concept of waqf. Investment and financing structures devised without proper consideration for the specific legal nature of waqf in Islamic law would invariably result in legal impossibilities that may nullify the investments, thus bringing possible loss upon financial institutions and their investors. Careful understanding of the precise nature of waqf and the implications of its legal nature, especially with regard to inalienability and non-transferabilility, on the modes and structures that could be employed in upgrading waqf assets is of paramount importance. The current research attempts to probe how certain modes of investment are not in keeping with the essential nature of waqf, and explore some alternative means wherein such weaknesses are not present.